EMPLOYEE ENGAGEMENT: A LITERATURE REVIEW - Deby Kurnia; Susi Hendriani (Fakultas Pertanian, Universitas Riau, 2023)
Employee involvement is an important factor in organizational success, which is able to drive productivity, innovation, and employee welfare. This literature review aims to provide a comprehensive overview of employee engagement, exploring the conceptualization, causes, outcomes, and measurement of employee engagement. The conceptualization of employee engagement involves the emotional, cognitive, and behavioral aspects of employee relationships and commitment to their work and organization. This includes factors such as job satisfaction, organizational commitment, and a sense of belonging. Many causes affect employee engagement including personality characteristics, job characteristics, and work environment. In addition, organizational factors such as leadership style, communication style, and organizational culture have a significant effect on the level of involvement. Employee engagement is complex and has far-reaching implications for organizations. Employees who are highly engaged tend to show higher job performance, increased organizational concern, and lower turnover. The article also identifies various employee engagement measurement approaches whose results can be used as evaluations for organizations to improve performance. Overall, this literature review provides a comprehensive overview of employee engagement, the Concept of Employee Engagement, Influencing factors, outcomes, and engagement measurement.